Twelve‐year follow‐up of conservative management of postnatal urinary and faecal incontinence and prolapse outcomes: randomised controlled trial. (22nd October 2013) - Glazener, CMA; MacArthur, C; Hagen, S; Elders, A; Lancashire, R; Herbison, GP; Wilson, PD; ,
<x xml:space="preserve">Abstract</x> Objective To determine the long‐term (12‐year) effects of a conservative nurse‐led intervention for postnatal urinary incontinence. Design Follow‐up of a randomised controlled trial. Setting Community‐based intervention in three centres (in the UK and New Zealand). Population A cohort of 747 women with urinary incontinence at 3 months after childbirth, of whom 471 (63%) were followed up after 12 years. Methods Women were randomly allocated to active conservative treatment after delivery (pelvic floor muscle training and bladder training), or to a control group receiving standard care. Main outcome measures Prevalence of urinary incontinence (primary outcome) and faecal incontinence, symptoms and signs of prolapse, and performance of pelvic floor muscle training at 12 years. Results The significant improvements relative to controls that had been found in urinary incontinence (60 versus 69%; risk difference, RD, −9.1%; 95% confidence interval, 95% CI, −17.3 to −1.0%) and faecal incontinence (4 versus 11%; RD −6.1%; 95% CI −10.8 to −1.6%) at 1 year did not persist for urinary incontinence (83 versus 80%; RD 2.1%; 95% CI −4.9 to 9.1%) or faecal incontinence (19 versus 15%; RD 4.3%; 95% CI −2.5 to 11.0%) at the 12–year follow up, irrespective of incontinence severity at trial entry. The prevalence of prolapse symptoms or objectively measured pelvic organ prolapse also did not differ between the groups. In the short term the intervention motivated more women to perform pelvic floor muscle training (83 versus 55%), but this fell in both groups by 12 years (52 versus 49%). Conclusions The moderate short‐term benefits of a brief nurse‐led conservative treatment for postnatal urinary incontinence did not persist. About four‐fifths of women with urinary incontinence 3 months after childbirth still had this problem 12 years later.